list.v 153 KB
Newer Older
Robbert Krebbers's avatar
Robbert Krebbers committed
1
(* Copyright (c) 2012-2015, Robbert Krebbers. *)
2 3 4
(* This file is distributed under the terms of the BSD license. *)
(** This file collects general purpose definitions and theorems on lists that
are not in the Coq standard library. *)
5
Require Export Permutation.
6
Require Export prelude.numbers prelude.base prelude.decidable prelude.option.
Robbert Krebbers's avatar
Robbert Krebbers committed
7

8
Arguments length {_} _.
Robbert Krebbers's avatar
Robbert Krebbers committed
9 10 11
Arguments cons {_} _ _.
Arguments app {_} _ _.
Arguments Permutation {_} _ _.
12
Arguments Forall_cons {_} _ _ _ _ _.
Robbert Krebbers's avatar
Robbert Krebbers committed
13

14 15 16
Notation tail := tl.
Notation take := firstn.
Notation drop := skipn.
17

18 19 20
Arguments take {_} !_ !_ /.
Arguments drop {_} !_ !_ /.

Robbert Krebbers's avatar
Robbert Krebbers committed
21 22 23 24 25 26 27
Notation "(::)" := cons (only parsing) : C_scope.
Notation "( x ::)" := (cons x) (only parsing) : C_scope.
Notation "(:: l )" := (λ x, cons x l) (only parsing) : C_scope.
Notation "(++)" := app (only parsing) : C_scope.
Notation "( l ++)" := (app l) (only parsing) : C_scope.
Notation "(++ k )" := (λ l, app l k) (only parsing) : C_scope.

28 29 30 31 32 33 34 35 36
Infix "≡ₚ" := Permutation (at level 70, no associativity) : C_scope.
Notation "(≡ₚ)" := Permutation (only parsing) : C_scope.
Notation "( x ≡ₚ)" := (Permutation x) (only parsing) : C_scope.
Notation "(≡ₚ x )" := (λ y, y ≡ₚ x) (only parsing) : C_scope.
Notation "(≢ₚ)" := (λ x y, ¬x ≡ₚ y) (only parsing) : C_scope.
Notation "x ≢ₚ y":= (¬x ≡ₚ y) (at level 70, no associativity) : C_scope.
Notation "( x ≢ₚ)" := (λ y, x ≢ₚ y) (only parsing) : C_scope.
Notation "(≢ₚ x )" := (λ y, y ≢ₚ x) (only parsing) : C_scope.

Robbert Krebbers's avatar
Robbert Krebbers committed
37 38 39
Instance maybe_cons {A} : Maybe2 (@cons A) := λ l,
  match l with x :: l => Some (x,l) | _ => None end.

40
(** * Definitions *)
41 42 43 44 45 46
(** Setoid equality lifted to lists *)
Inductive list_equiv `{Equiv A} : Equiv (list A) :=
  | nil_equiv : [] ≡ []
  | cons_equiv x y l k : x ≡ y → l ≡ k → x :: l ≡ y :: k.
Existing Instance list_equiv.

47 48
(** The operation [l !! i] gives the [i]th element of the list [l], or [None]
in case [i] is out of bounds. *)
Robbert Krebbers's avatar
Robbert Krebbers committed
49
Instance list_lookup {A} : Lookup nat A (list A) :=
50
  fix go i l {struct l} : option A := let _ : Lookup _ _ _ := @go in
51
  match l with
52
  | [] => None | x :: l => match i with 0 => Some x | S i => l !! i end
53
  end.
54 55 56

(** The operation [alter f i l] applies the function [f] to the [i]th element
of [l]. In case [i] is out of bounds, the list is returned unchanged. *)
57 58
Instance list_alter {A} : Alter nat A (list A) := λ f,
  fix go i l {struct l} :=
59 60
  match l with
  | [] => []
61
  | x :: l => match i with 0 => f x :: l | S i => x :: go i l end
62
  end.
63

64 65
(** The operation [<[i:=x]> l] overwrites the element at position [i] with the
value [x]. In case [i] is out of bounds, the list is returned unchanged. *)
66 67 68 69 70 71
Instance list_insert {A} : Insert nat A (list A) :=
  fix go i y l {struct l} := let _ : Insert _ _ _ := @go in
  match l with
  | [] => []
  | x :: l => match i with 0 => y :: l | S i => x :: <[i:=y]>l end
  end.
72 73 74 75 76
Fixpoint list_inserts {A} (i : nat) (k l : list A) : list A :=
  match k with
  | [] => l
  | y :: k => <[i:=y]>(list_inserts (S i) k l)
  end.
77

78 79 80
(** The operation [delete i l] removes the [i]th element of [l] and moves
all consecutive elements one position ahead. In case [i] is out of bounds,
the list is returned unchanged. *)
81 82
Instance list_delete {A} : Delete nat (list A) :=
  fix go (i : nat) (l : list A) {struct l} : list A :=
83 84
  match l with
  | [] => []
85
  | x :: l => match i with 0 => l | S i => x :: @delete _ _ go i l end
86
  end.
87 88 89

(** The function [option_list o] converts an element [Some x] into the
singleton list [[x]], and [None] into the empty list [[]]. *)
Robbert Krebbers's avatar
Robbert Krebbers committed
90
Definition option_list {A} : option A → list A := option_rect _ (λ x, [x]) [].
91 92
Definition list_singleton {A} (l : list A) : option A :=
  match l with [x] => Some x | _ => None end.
Robbert Krebbers's avatar
Robbert Krebbers committed
93 94 95 96

(** The function [filter P l] returns the list of elements of [l] that
satisfies [P]. The order remains unchanged. *)
Instance list_filter {A} : Filter A (list A) :=
97
  fix go P _ l := let _ : Filter _ _ := @go in
Robbert Krebbers's avatar
Robbert Krebbers committed
98 99
  match l with
  | [] => []
100
  | x :: l => if decide (P x) then x :: filter P l else filter P l
101 102 103 104
  end.

(** The function [list_find P l] returns the first index [i] whose element
satisfies the predicate [P]. *)
105
Definition list_find {A} P `{∀ x, Decision (P x)} : list A → option (nat * A) :=
106 107
  fix go l :=
  match l with
108 109
  | [] => None
  | x :: l => if decide (P x) then Some (0,x) else prod_map S id <$> go l
110
  end.
Robbert Krebbers's avatar
Robbert Krebbers committed
111 112 113 114

(** The function [replicate n x] generates a list with length [n] of elements
with value [x]. *)
Fixpoint replicate {A} (n : nat) (x : A) : list A :=
115
  match n with 0 => [] | S n => x :: replicate n x end.
Robbert Krebbers's avatar
Robbert Krebbers committed
116 117 118 119

(** The function [reverse l] returns the elements of [l] in reverse order. *)
Definition reverse {A} (l : list A) : list A := rev_append l [].

120 121 122 123
(** The function [last l] returns the last element of the list [l], or [None]
if the list [l] is empty. *)
Fixpoint last {A} (l : list A) : option A :=
  match l with [] => None | [x] => Some x | _ :: l => last l end.
124

Robbert Krebbers's avatar
Robbert Krebbers committed
125 126 127 128 129 130
(** The function [resize n y l] takes the first [n] elements of [l] in case
[length l ≤ n], and otherwise appends elements with value [x] to [l] to obtain
a list of length [n]. *)
Fixpoint resize {A} (n : nat) (y : A) (l : list A) : list A :=
  match l with
  | [] => replicate n y
131
  | x :: l => match n with 0 => [] | S n => x :: resize n y l end
Robbert Krebbers's avatar
Robbert Krebbers committed
132 133 134
  end.
Arguments resize {_} !_ _ !_.

135 136 137
(** The function [reshape k l] transforms [l] into a list of lists whose sizes
are specified by [k]. In case [l] is too short, the resulting list will be
padded with empty lists. In case [l] is too long, it will be truncated. *)
138 139
Fixpoint reshape {A} (szs : list nat) (l : list A) : list (list A) :=
  match szs with
140
  | [] => [] | sz :: szs => take sz l :: reshape szs (drop sz l)
141 142
  end.

143
Definition sublist_lookup {A} (i n : nat) (l : list A) : option (list A) :=
144 145 146 147
  guard (i + n ≤ length l); Some (take n (drop i l)).
Definition sublist_alter {A} (f : list A → list A)
    (i n : nat) (l : list A) : list A :=
  take i l ++ f (take n (drop i l)) ++ drop (i + n) l.
148

149 150 151 152
(** Functions to fold over a list. We redefine [foldl] with the arguments in
the same order as in Haskell. *)
Notation foldr := fold_right.
Definition foldl {A B} (f : A → B → A) : A → list B → A :=
153
  fix go a l := match l with [] => a | x :: l => go (f a x) l end.
154 155 156

(** The monadic operations. *)
Instance list_ret: MRet list := λ A x, x :: @nil A.
157 158
Instance list_fmap : FMap list := λ A B f,
  fix go (l : list A) := match l with [] => [] | x :: l => f x :: go l end.
159 160 161 162 163 164
Instance list_omap : OMap list := λ A B f,
  fix go (l : list A) :=
  match l with
  | [] => []
  | x :: l => match f x with Some y => y :: go l | None => go l end
  end.
165 166
Instance list_bind : MBind list := λ A B f,
  fix go (l : list A) := match l with [] => [] | x :: l => f x ++ go l end.
167 168
Instance list_join: MJoin list :=
  fix go A (ls : list (list A)) : list A :=
169
  match ls with [] => [] | l :: ls => l ++ @mjoin _ go _ ls end.
170
Definition mapM `{MBind M, MRet M} {A B} (f : A → M B) : list A → M (list B) :=
171
  fix go l :=
172
  match l with [] => mret [] | x :: l => y ← f x; k ← go l; mret (y :: k) end.
173 174 175 176 177

(** We define stronger variants of map and fold that allow the mapped
function to use the index of the elements. *)
Definition imap_go {A B} (f : nat → A → B) : nat → list A → list B :=
  fix go (n : nat) (l : list A) :=
178
  match l with [] => [] | x :: l => f n x :: go (S n) l end.
179
Definition imap {A B} (f : nat → A → B) : list A → list B := imap_go f 0.
180 181 182 183
Definition zipped_map {A B} (f : list A → list A → A → B) :
  list A → list A → list B := fix go l k :=
  match k with [] => [] | x :: k => f l k x :: go (x :: l) k end.

Robbert Krebbers's avatar
Robbert Krebbers committed
184 185 186 187 188 189 190 191 192
Definition imap2_go {A B C} (f : nat → A → B → C) :
    nat → list A → list B → list C:=
  fix go (n : nat) (l : list A) (k : list B) :=
  match l, k with
  | [], _ |_, [] => [] | x :: l, y :: k => f n x y :: go (S n) l k
  end.
Definition imap2 {A B C} (f : nat → A → B → C) :
  list A → list B → list C := imap2_go f 0.

193 194 195 196 197 198 199
Inductive zipped_Forall {A} (P : list A → list A → A → Prop) :
    list A → list A → Prop :=
  | zipped_Forall_nil l : zipped_Forall P l []
  | zipped_Forall_cons l k x :
     P l k x → zipped_Forall P (x :: l) k → zipped_Forall P l (x :: k).
Arguments zipped_Forall_nil {_ _} _.
Arguments zipped_Forall_cons {_ _} _ _ _ _ _.
200

201 202 203 204 205 206 207
(** The function [mask f βs l] applies the function [f] to elements in [l] at
positions that are [true] in [βs]. *)
Fixpoint mask {A} (f : A → A) (βs : list bool) (l : list A) : list A :=
  match βs, l with
  | β :: βs, x :: l => (if β then f x else x) :: mask f βs l
  | _, _ => l
  end.
208 209 210 211

(** The function [permutations l] yields all permutations of [l]. *)
Fixpoint interleave {A} (x : A) (l : list A) : list (list A) :=
  match l with
212
  | [] => [[x]]| y :: l => (x :: y :: l) :: ((y ::) <$> interleave x l)
213 214
  end.
Fixpoint permutations {A} (l : list A) : list (list A) :=
215
  match l with [] => [[]] | x :: l => permutations l ≫= interleave x end.
216

217 218
(** The predicate [suffix_of] holds if the first list is a suffix of the second.
The predicate [prefix_of] holds if the first list is a prefix of the second. *)
219 220
Definition suffix_of {A} : relation (list A) := λ l1 l2, ∃ k, l2 = k ++ l1.
Definition prefix_of {A} : relation (list A) := λ l1 l2, ∃ k, l2 = l1 ++ k.
221 222
Infix "`suffix_of`" := suffix_of (at level 70) : C_scope.
Infix "`prefix_of`" := prefix_of (at level 70) : C_scope.
223 224
Hint Extern 0 (_ `prefix_of` _) => reflexivity.
Hint Extern 0 (_ `suffix_of` _) => reflexivity.
Robbert Krebbers's avatar
Robbert Krebbers committed
225

226 227 228 229 230 231 232 233
Section prefix_suffix_ops.
  Context `{∀ x y : A, Decision (x = y)}.
  Definition max_prefix_of : list A → list A → list A * list A * list A :=
    fix go l1 l2 :=
    match l1, l2 with
    | [], l2 => ([], l2, [])
    | l1, [] => (l1, [], [])
    | x1 :: l1, x2 :: l2 =>
234
      if decide_rel (=) x1 x2
235
      then prod_map id (x1 ::) (go l1 l2) else (x1 :: l1, x2 :: l2, [])
236 237 238 239 240
    end.
  Definition max_suffix_of (l1 l2 : list A) : list A * list A * list A :=
    match max_prefix_of (reverse l1) (reverse l2) with
    | (k1, k2, k3) => (reverse k1, reverse k2, reverse k3)
    end.
241 242
  Definition strip_prefix (l1 l2 : list A) := (max_prefix_of l1 l2).1.2.
  Definition strip_suffix (l1 l2 : list A) := (max_suffix_of l1 l2).1.2.
243
End prefix_suffix_ops.
Robbert Krebbers's avatar
Robbert Krebbers committed
244

245
(** A list [l1] is a sublist of [l2] if [l2] is obtained by removing elements
246 247 248
from [l1] without changing the order. *)
Inductive sublist {A} : relation (list A) :=
  | sublist_nil : sublist [] []
249
  | sublist_skip x l1 l2 : sublist l1 l2 → sublist (x :: l1) (x :: l2)
250
  | sublist_cons x l1 l2 : sublist l1 l2 → sublist l1 (x :: l2).
251
Infix "`sublist`" := sublist (at level 70) : C_scope.
252
Hint Extern 0 (_ `sublist` _) => reflexivity.
253 254

(** A list [l2] contains a list [l1] if [l2] is obtained by removing elements
255
from [l1] while possiblity changing the order. *)
256 257 258 259
Inductive contains {A} : relation (list A) :=
  | contains_nil : contains [] []
  | contains_skip x l1 l2 : contains l1 l2 → contains (x :: l1) (x :: l2)
  | contains_swap x y l : contains (y :: x :: l) (x :: y :: l)
260
  | contains_cons x l1 l2 : contains l1 l2 → contains l1 (x :: l2)
261 262
  | contains_trans l1 l2 l3 : contains l1 l2 → contains l2 l3 → contains l1 l3.
Infix "`contains`" := contains (at level 70) : C_scope.
263
Hint Extern 0 (_ `contains` _) => reflexivity.
264 265 266 267 268 269 270 271 272 273

Section contains_dec_help.
  Context {A} {dec : ∀ x y : A, Decision (x = y)}.
  Fixpoint list_remove (x : A) (l : list A) : option (list A) :=
    match l with
    | [] => None
    | y :: l => if decide (x = y) then Some l else (y ::) <$> list_remove x l
    end.
  Fixpoint list_remove_list (k : list A) (l : list A) : option (list A) :=
    match k with
274
    | [] => Some l | x :: k => list_remove x l ≫= list_remove_list k
275 276
    end.
End contains_dec_help.
277

278 279 280 281 282
Inductive Forall3 {A B C} (P : A → B → C → Prop) :
     list A → list B → list C → Prop :=
  | Forall3_nil : Forall3 P [] [] []
  | Forall3_cons x y z l k k' :
     P x y z → Forall3 P l k k' → Forall3 P (x :: l) (y :: k) (z :: k').
283 284 285 286 287 288 289 290 291 292 293 294 295 296 297 298 299 300 301 302 303 304 305 306 307

(** Set operations on lists *)
Section list_set.
  Context {A} {dec : ∀ x y : A, Decision (x = y)}.
  Global Instance elem_of_list_dec {dec : ∀ x y : A, Decision (x = y)}
    (x : A) : ∀ l, Decision (x ∈ l).
  Proof.
   refine (
    fix go l :=
    match l return Decision (x ∈ l) with
    | [] => right _
    | y :: l => cast_if_or (decide (x = y)) (go l)
    end); clear go dec; subst; try (by constructor); abstract by inversion 1.
  Defined.
  Fixpoint remove_dups (l : list A) : list A :=
    match l with
    | [] => []
    | x :: l =>
      if decide_rel (∈) x l then remove_dups l else x :: remove_dups l
    end.
  Fixpoint list_difference (l k : list A) : list A :=
    match l with
    | [] => []
    | x :: l =>
      if decide_rel (∈) x k
308
      then list_difference l k else x :: list_difference l k
309
    end.
310
  Definition list_union (l k : list A) : list A := list_difference l k ++ k.
311 312 313 314 315
  Fixpoint list_intersection (l k : list A) : list A :=
    match l with
    | [] => []
    | x :: l =>
      if decide_rel (∈) x k
316
      then x :: list_intersection l k else list_intersection l k
317 318 319 320 321 322 323 324 325
    end.
  Definition list_intersection_with (f : A → A → option A) :
    list A → list A → list A := fix go l k :=
    match l with
    | [] => []
    | x :: l => foldr (λ y,
        match f x y with None => id | Some z => (z ::) end) (go l k) k
    end.
End list_set.
326 327

(** * Basic tactics on lists *)
328 329 330
(** The tactic [discriminate_list_equality] discharges a goal if it contains
a list equality involving [(::)] and [(++)] of two lists that have a different
length as one of its hypotheses. *)
331 332
Tactic Notation "discriminate_list_equality" hyp(H) :=
  apply (f_equal length) in H;
333
  repeat (csimpl in H || rewrite app_length in H); exfalso; lia.
334
Tactic Notation "discriminate_list_equality" :=
335 336 337
  match goal with
  | H : @eq (list _) _ _ |- _ => discriminate_list_equality H
  end.
338

339 340 341
(** The tactic [simplify_list_equality] simplifies hypotheses involving
equalities on lists using injectivity of [(::)] and [(++)]. Also, it simplifies
lookups in singleton lists. *)
342
Lemma app_inj_1 {A} (l1 k1 l2 k2 : list A) :
343 344
  length l1 = length k1 → l1 ++ l2 = k1 ++ k2 → l1 = k1 ∧ l2 = k2.
Proof. revert k1. induction l1; intros [|??]; naive_solver. Qed.
345
Lemma app_inj_2 {A} (l1 k1 l2 k2 : list A) :
346 347
  length l2 = length k2 → l1 ++ l2 = k1 ++ k2 → l1 = k1 ∧ l2 = k2.
Proof.
348
  intros ? Hl. apply app_inj_1; auto.
349 350
  apply (f_equal length) in Hl. rewrite !app_length in Hl. lia.
Qed.
351
Ltac simplify_list_equality :=
352
  repeat match goal with
353
  | _ => progress simplify_equality'
354
  | H : _ ++ _ = _ ++ _ |- _ => first
355
    [ apply app_inv_head in H | apply app_inv_tail in H
356 357
    | apply app_inj_1 in H; [destruct H|done]
    | apply app_inj_2 in H; [destruct H|done] ]
Robbert Krebbers's avatar
Robbert Krebbers committed
358
  | H : [?x] !! ?i = Some ?y |- _ =>
359
    destruct i; [change (Some x = Some y) in H | discriminate]
360
  end.
361

362 363
(** * General theorems *)
Section general_properties.
Robbert Krebbers's avatar
Robbert Krebbers committed
364
Context {A : Type}.
365 366
Implicit Types x y z : A.
Implicit Types l k : list A.
Robbert Krebbers's avatar
Robbert Krebbers committed
367

368 369 370 371 372 373 374 375 376 377 378 379 380 381 382 383 384 385
Section setoid.
  Context `{Equiv A} `{!Equivalence ((≡) : relation A)}.
  Global Instance map_equivalence : Equivalence ((≡) : relation (list A)).
  Proof.
    split.
    * intros l; induction l; constructor; auto.
    * induction 1; constructor; auto.
    * intros l1 l2 l3 Hl; revert l3.
      induction Hl; inversion_clear 1; constructor; try etransitivity; eauto.
  Qed.
  Global Instance cons_proper : Proper ((≡) ==> (≡) ==> (≡)) (@cons A).
  Proof. by constructor. Qed.
  Global Instance app_proper : Proper ((≡) ==> (≡) ==> (≡)) (@app A).
  Proof.
    induction 1 as [|x y l k ?? IH]; intros ?? Htl; simpl; auto.
    by apply cons_equiv, IH.
  Qed.
  Global Instance list_leibniz `{!LeibnizEquiv A} : LeibnizEquiv (list A).
386
  Proof. induction 1; f_equal; fold_leibniz; auto. Qed.
387 388
End setoid.

389
Global Instance: Inj2 (=) (=) (=) (@cons A).
390
Proof. by injection 1. Qed.
391
Global Instance: ∀ k, Inj (=) (=) (k ++).
392
Proof. intros ???. apply app_inv_head. Qed.
393
Global Instance: ∀ k, Inj (=) (=) (++ k).
394
Proof. intros ???. apply app_inv_tail. Qed.
395
Global Instance: Assoc (=) (@app A).
396 397 398 399 400
Proof. intros ???. apply app_assoc. Qed.
Global Instance: LeftId (=) [] (@app A).
Proof. done. Qed.
Global Instance: RightId (=) [] (@app A).
Proof. intro. apply app_nil_r. Qed.
401

402
Lemma app_nil l1 l2 : l1 ++ l2 = [] ↔ l1 = [] ∧ l2 = [].
403
Proof. split. apply app_eq_nil. by intros [-> ->]. Qed.
404 405
Lemma app_singleton l1 l2 x :
  l1 ++ l2 = [x] ↔ l1 = [] ∧ l2 = [x] ∨ l1 = [x] ∧ l2 = [].
406
Proof. split. apply app_eq_unit. by intros [[-> ->]|[-> ->]]. Qed.
407 408 409
Lemma cons_middle x l1 l2 : l1 ++ x :: l2 = l1 ++ [x] ++ l2.
Proof. done. Qed.
Lemma list_eq l1 l2 : (∀ i, l1 !! i = l2 !! i) → l1 = l2.
410 411
Proof.
  revert l2. induction l1; intros [|??] H.
412
  * done.
413 414
  * discriminate (H 0).
  * discriminate (H 0).
415
  * f_equal; [by injection (H 0)|]. apply (IHl1 _ $ λ i, H (S i)).
416
Qed.
417
Global Instance list_eq_dec {dec : ∀ x y, Decision (x = y)} : ∀ l k,
418
  Decision (l = k) := list_eq_dec dec.
419 420 421 422 423 424 425 426
Global Instance list_eq_nil_dec l : Decision (l = []).
Proof. by refine match l with [] => left _ | _ => right _ end. Defined.
Lemma list_singleton_reflect l :
  option_reflect (λ x, l = [x]) (length l ≠ 1) (list_singleton l).
Proof. by destruct l as [|? []]; constructor. Defined.

Definition nil_length : length (@nil A) = 0 := eq_refl.
Definition cons_length x l : length (x :: l) = S (length l) := eq_refl.
427
Lemma nil_or_length_pos l : l = [] ∨ length l ≠ 0.
428
Proof. destruct l; simpl; auto with lia. Qed.
429
Lemma nil_length_inv l : length l = 0 → l = [].
430 431
Proof. by destruct l. Qed.
Lemma lookup_nil i : @nil A !! i = None.
432
Proof. by destruct i. Qed.
433
Lemma lookup_tail l i : tail l !! i = l !! S i.
434
Proof. by destruct l. Qed.
435 436
Lemma lookup_lt_Some l i x : l !! i = Some x → i < length l.
Proof.
437
  revert i. induction l; intros [|?] ?; simplify_equality'; auto with arith.
438 439 440 441 442
Qed.
Lemma lookup_lt_is_Some_1 l i : is_Some (l !! i) → i < length l.
Proof. intros [??]; eauto using lookup_lt_Some. Qed.
Lemma lookup_lt_is_Some_2 l i : i < length l → is_Some (l !! i).
Proof.
443
  revert i. induction l; intros [|?] ?; simplify_equality'; eauto with lia.
444 445 446 447 448 449 450 451 452
Qed.
Lemma lookup_lt_is_Some l i : is_Some (l !! i) ↔ i < length l.
Proof. split; auto using lookup_lt_is_Some_1, lookup_lt_is_Some_2. Qed.
Lemma lookup_ge_None l i : l !! i = None ↔ length l ≤ i.
Proof. rewrite eq_None_not_Some, lookup_lt_is_Some. lia. Qed.
Lemma lookup_ge_None_1 l i : l !! i = None → length l ≤ i.
Proof. by rewrite lookup_ge_None. Qed.
Lemma lookup_ge_None_2 l i : length l ≤ i → l !! i = None.
Proof. by rewrite lookup_ge_None. Qed.
453 454 455
Lemma list_eq_same_length l1 l2 n :
  length l2 = n → length l1 = n →
  (∀ i x y, i < n → l1 !! i = Some x → l2 !! i = Some y → x = y) → l1 = l2.
Robbert Krebbers's avatar
Robbert Krebbers committed
456
Proof.
457 458 459 460 461
  intros <- Hlen Hl; apply list_eq; intros i. destruct (l2 !! i) as [x|] eqn:Hx.
  * destruct (lookup_lt_is_Some_2 l1 i) as [y Hy].
    { rewrite Hlen; eauto using lookup_lt_Some. }
    rewrite Hy; f_equal; apply (Hl i); eauto using lookup_lt_Some.
  * by rewrite lookup_ge_None, Hlen, <-lookup_ge_None.
Robbert Krebbers's avatar
Robbert Krebbers committed
462
Qed.
463
Lemma lookup_app_l l1 l2 i : i < length l1 → (l1 ++ l2) !! i = l1 !! i.
464
Proof. revert i. induction l1; intros [|?]; simpl; auto with lia. Qed.
465 466
Lemma lookup_app_l_Some l1 l2 i x : l1 !! i = Some x → (l1 ++ l2) !! i = Some x.
Proof. intros. rewrite lookup_app_l; eauto using lookup_lt_Some. Qed.
467
Lemma lookup_app_r l1 l2 i :
468
  length l1 ≤ i → (l1 ++ l2) !! i = l2 !! (i - length l1).
469 470 471 472 473 474 475 476 477 478 479
Proof. revert i. induction l1; intros [|?]; simpl; auto with lia. Qed.
Lemma lookup_app_Some l1 l2 i x :
  (l1 ++ l2) !! i = Some x ↔
    l1 !! i = Some x ∨ length l1 ≤ i ∧ l2 !! (i - length l1) = Some x.
Proof.
  split.
  * revert i. induction l1 as [|y l1 IH]; intros [|i] ?;
      simplify_equality'; auto with lia.
    destruct (IH i) as [?|[??]]; auto with lia.
  * intros [?|[??]]; auto using lookup_app_l_Some. by rewrite lookup_app_r.
Qed.
480 481 482
Lemma list_lookup_middle l1 l2 x n :
  n = length l1 → (l1 ++ x :: l2) !! n = Some x.
Proof. intros ->. by induction l1. Qed.
483

484 485
Lemma list_insert_alter l i x : <[i:=x]>l = alter (λ _, x) i l.
Proof. by revert i; induction l; intros []; intros; f_equal'. Qed.
486
Lemma alter_length f l i : length (alter f i l) = length l.
487
Proof. revert i. by induction l; intros [|?]; f_equal'. Qed.
488
Lemma insert_length l i x : length (<[i:=x]>l) = length l.
489
Proof. revert i. by induction l; intros [|?]; f_equal'. Qed.
490
Lemma list_lookup_alter f l i : alter f i l !! i = f <$> l !! i.
491
Proof. revert i. induction l. done. intros [|i]. done. apply (IHl i). Qed.
Robbert Krebbers's avatar
Robbert Krebbers committed
492
Lemma list_lookup_alter_ne f l i j : i ≠ j → alter f i l !! j = l !! j.
493
Proof.
494
  revert i j. induction l; [done|]. intros [][] ?; csimpl; auto with congruence.
495
Qed.
496
Lemma list_lookup_insert l i x : i < length l → <[i:=x]>l !! i = Some x.
497 498
Proof. revert i. induction l; intros [|?] ?; f_equal'; auto with lia. Qed.
Lemma list_lookup_insert_ne l i j x : i ≠ j → <[i:=x]>l !! j = l !! j.
499
Proof.
500
  revert i j. induction l; [done|]. intros [] [] ?; simpl; auto with congruence.
501
Qed.
502 503 504 505 506 507 508 509 510 511 512 513 514 515
Lemma list_lookup_insert_Some l i x j y :
  <[i:=x]>l !! j = Some y ↔
    i = j ∧ x = y ∧ j < length l ∨ i ≠ j ∧ l !! j = Some y.
Proof.
  destruct (decide (i = j)) as [->|];
    [split|rewrite list_lookup_insert_ne by done; tauto].
  * intros Hy. assert (j < length l).
    { rewrite <-(insert_length l j x); eauto using lookup_lt_Some. }
    rewrite list_lookup_insert in Hy by done; naive_solver.
  * intros [(?&?&?)|[??]]; rewrite ?list_lookup_insert; naive_solver.
Qed.
Lemma list_insert_commute l i j x y :
  i ≠ j → <[i:=x]>(<[j:=y]>l) = <[j:=y]>(<[i:=x]>l).
Proof. revert i j. by induction l; intros [|?] [|?] ?; f_equal'; auto. Qed.
516 517
Lemma list_lookup_other l i x :
  length l ≠ 1 → l !! i = Some x → ∃ j y, j ≠ i ∧ l !! j = Some y.
Robbert Krebbers's avatar
Robbert Krebbers committed
518
Proof.
519
  intros. destruct i, l as [|x0 [|x1 l]]; simplify_equality'.
520 521
  * by exists 1, x1.
  * by exists 0, x0.
Robbert Krebbers's avatar
Robbert Krebbers committed
522
Qed.
523 524
Lemma alter_app_l f l1 l2 i :
  i < length l1 → alter f i (l1 ++ l2) = alter f i l1 ++ l2.
525
Proof. revert i. induction l1; intros [|?] ?; f_equal'; auto with lia. Qed.
526
Lemma alter_app_r f l1 l2 i :
527
  alter f (length l1 + i) (l1 ++ l2) = l1 ++ alter f i l2.
528
Proof. revert i. induction l1; intros [|?]; f_equal'; auto. Qed.
529 530
Lemma alter_app_r_alt f l1 l2 i :
  length l1 ≤ i → alter f i (l1 ++ l2) = l1 ++ alter f (i - length l1) l2.
531 532 533 534
Proof.
  intros. assert (i = length l1 + (i - length l1)) as Hi by lia.
  rewrite Hi at 1. by apply alter_app_r.
Qed.
535 536
Lemma list_alter_id f l i : (∀ x, f x = x) → alter f i l = l.
Proof. intros ?. revert i. induction l; intros [|?]; f_equal'; auto. Qed.
537 538 539
Lemma list_alter_ext f g l k i :
  (∀ x, l !! i = Some x → f x = g x) → l = k → alter f i l = alter g i k.
Proof. intros H ->. revert i H. induction k; intros [|?] ?; f_equal'; auto. Qed.
540 541
Lemma list_alter_compose f g l i :
  alter (f ∘ g) i l = alter f i (alter g i l).
542
Proof. revert i. induction l; intros [|?]; f_equal'; auto. Qed.
543 544
Lemma list_alter_commute f g l i j :
  i ≠ j → alter f i (alter g j l) = alter g j (alter f i l).
545
Proof. revert i j. induction l; intros [|?][|?] ?; f_equal'; auto with lia. Qed.
546 547
Lemma insert_app_l l1 l2 i x :
  i < length l1 → <[i:=x]>(l1 ++ l2) = <[i:=x]>l1 ++ l2.
548
Proof. revert i. induction l1; intros [|?] ?; f_equal'; auto with lia. Qed.
549
Lemma insert_app_r l1 l2 i x : <[length l1+i:=x]>(l1 ++ l2) = l1 ++ <[i:=x]>l2.
550
Proof. revert i. induction l1; intros [|?]; f_equal'; auto. Qed.
551 552
Lemma insert_app_r_alt l1 l2 i x :
  length l1 ≤ i → <[i:=x]>(l1 ++ l2) = l1 ++ <[i - length l1:=x]>l2.
553 554 555 556
Proof.
  intros. assert (i = length l1 + (i - length l1)) as Hi by lia.
  rewrite Hi at 1. by apply insert_app_r.
Qed.
557
Lemma delete_middle l1 l2 x : delete (length l1) (l1 ++ x :: l2) = l1 ++ l2.
558
Proof. induction l1; f_equal'; auto. Qed.
559

560 561 562 563 564 565 566 567 568 569 570 571 572 573 574 575 576 577 578 579 580 581 582 583 584 585 586 587 588 589 590 591 592 593 594 595 596 597 598 599 600 601 602 603 604 605 606 607 608
Lemma inserts_length l i k : length (list_inserts i k l) = length l.
Proof.
  revert i. induction k; intros ?; csimpl; rewrite ?insert_length; auto.
Qed.
Lemma list_lookup_inserts l i k j :
  i ≤ j < i + length k → j < length l →
  list_inserts i k l !! j = k !! (j - i).
Proof.
  revert i j. induction k as [|y k IH]; csimpl; intros i j ??; [lia|].
  destruct (decide (i = j)) as [->|].
  { by rewrite list_lookup_insert, Nat.sub_diag
      by (rewrite inserts_length; lia). }
  rewrite list_lookup_insert_ne, IH by lia.
  by replace (j - i) with (S (j - S i)) by lia.
Qed.
Lemma list_lookup_inserts_lt l i k j :
  j < i → list_inserts i k l !! j = l !! j.
Proof.
  revert i j. induction k; intros i j ?; csimpl;
    rewrite ?list_lookup_insert_ne by lia; auto with lia.
Qed.
Lemma list_lookup_inserts_ge l i k j :
  i + length k ≤ j → list_inserts i k l !! j = l !! j.
Proof.
  revert i j. induction k; csimpl; intros i j ?;
    rewrite ?list_lookup_insert_ne by lia; auto with lia.
Qed.
Lemma list_lookup_inserts_Some l i k j y :
  list_inserts i k l !! j = Some y ↔
    (j < i ∨ i + length k ≤ j) ∧ l !! j = Some y ∨
    i ≤ j < i + length k ∧ j < length l ∧ k !! (j - i) = Some y.
Proof.
  destruct (decide (j < i)).
  { rewrite list_lookup_inserts_lt by done; intuition lia. }
  destruct (decide (i + length k ≤ j)).
  { rewrite list_lookup_inserts_ge by done; intuition lia. }
  split.
  * intros Hy. assert (j < length l).
    { rewrite <-(inserts_length l i k); eauto using lookup_lt_Some. }
    rewrite list_lookup_inserts in Hy by lia. intuition lia.
  * intuition. by rewrite list_lookup_inserts by lia.
Qed.
Lemma list_insert_inserts_lt l i j x k :
  i < j → <[i:=x]>(list_inserts j k l) = list_inserts j k (<[i:=x]>l).
Proof.
  revert i j. induction k; intros i j ?; simpl;
    rewrite 1?list_insert_commute by lia; auto with f_equal.
Qed.

609
(** ** Properties of the [elem_of] predicate *)
610
Lemma not_elem_of_nil x : x ∉ [].
611
Proof. by inversion 1. Qed.
612
Lemma elem_of_nil x : x ∈ [] ↔ False.
613
Proof. intuition. by destruct (not_elem_of_nil x). Qed.
614
Lemma elem_of_nil_inv l : (∀ x, x ∉ l) → l = [].
615
Proof. destruct l. done. by edestruct 1; constructor. Qed.
616 617
Lemma elem_of_not_nil x l : x ∈ l → l ≠ [].
Proof. intros ? ->. by apply (elem_of_nil x). Qed.
618
Lemma elem_of_cons l x y : x ∈ y :: l ↔ x = y ∨ x ∈ l.
Robbert Krebbers's avatar
Robbert Krebbers committed
619
Proof. by split; [inversion 1; subst|intros [->|?]]; constructor. Qed.
620
Lemma not_elem_of_cons l x y : x ∉ y :: l ↔ x ≠ y ∧ x ∉ l.
Robbert Krebbers's avatar
Robbert Krebbers committed
621
Proof. rewrite elem_of_cons. tauto. Qed.
622
Lemma elem_of_app l1 l2 x : x ∈ l1 ++ l2 ↔ x ∈ l1 ∨ x ∈ l2.
623
Proof.
624
  induction l1.
625
  * split; [by right|]. intros [Hx|]; [|done]. by destruct (elem_of_nil x).
626
  * simpl. rewrite !elem_of_cons, IHl1. tauto.
627
Qed.
628
Lemma not_elem_of_app l1 l2 x : x ∉ l1 ++ l2 ↔ x ∉ l1 ∧ x ∉ l2.
Robbert Krebbers's avatar
Robbert Krebbers committed
629
Proof. rewrite elem_of_app. tauto. Qed.
630
Lemma elem_of_list_singleton x y : x ∈ [y] ↔ x = y.
631
Proof. rewrite elem_of_cons, elem_of_nil. tauto. Qed.
Robbert Krebbers's avatar
Robbert Krebbers committed
632
Global Instance elem_of_list_permutation_proper x : Proper ((≡ₚ) ==> iff) (x ∈).
633
Proof. induction 1; rewrite ?elem_of_nil, ?elem_of_cons; intuition. Qed.
634
Lemma elem_of_list_split l x : x ∈ l → ∃ l1 l2, l = l1 ++ x :: l2.
635
Proof.
636
  induction 1 as [x l|x y l ? [l1 [l2 ->]]]; [by eexists [], l|].
637
  by exists (y :: l1), l2.
638
Qed.
639
Lemma elem_of_list_lookup_1 l x : x ∈ l → ∃ i, l !! i = Some x.
640
Proof.
641 642
  induction 1 as [|???? IH]; [by exists 0 |].
  destruct IH as [i ?]; auto. by exists (S i).
643
Qed.
644
Lemma elem_of_list_lookup_2 l i x : l !! i = Some x → x ∈ l.
645
Proof.
646
  revert i. induction l; intros [|i] ?; simplify_equality'; constructor; eauto.
647
Qed.
648 649
Lemma elem_of_list_lookup l x : x ∈ l ↔ ∃ i, l !! i = Some x.
Proof. firstorder eauto using elem_of_list_lookup_1, elem_of_list_lookup_2. Qed.
650 651 652 653 654 655
Lemma elem_of_list_omap {B} (f : A → option B) l (y : B) :
  y ∈ omap f l ↔ ∃ x, x ∈ l ∧ f x = Some y.
Proof.
  split.
  * induction l as [|x l]; csimpl; repeat case_match; inversion 1; subst;
      setoid_rewrite elem_of_cons; naive_solver.
Robbert Krebbers's avatar
Robbert Krebbers committed
656 657
  * intros (x&Hx&?). by induction Hx; csimpl; repeat case_match;
      simplify_equality; try constructor; auto.
658
Qed.
659

660
(** ** Properties of the [NoDup] predicate *)
661 662
Lemma NoDup_nil : NoDup (@nil A) ↔ True.
Proof. split; constructor. Qed.
663
Lemma NoDup_cons x l : NoDup (x :: l) ↔ x ∉ l ∧ NoDup l.
664
Proof. split. by inversion 1. intros [??]. by constructor. Qed.
665
Lemma NoDup_cons_11 x l : NoDup (x :: l) → x ∉ l.
666
Proof. rewrite NoDup_cons. by intros [??]. Qed.
667
Lemma NoDup_cons_12 x l : NoDup (x :: l) → NoDup l.
668
Proof. rewrite NoDup_cons. by intros [??]. Qed.
669
Lemma NoDup_singleton x : NoDup [x].
670
Proof. constructor. apply not_elem_of_nil. constructor. Qed.
671
Lemma NoDup_app l k : NoDup (l ++ k) ↔ NoDup l ∧ (∀ x, x ∈ l → x ∉ k) ∧ NoDup k.
Robbert Krebbers's avatar
Robbert Krebbers committed
672
Proof.
673
  induction l; simpl.
674
  * rewrite NoDup_nil. setoid_rewrite elem_of_nil. naive_solver.
675
  * rewrite !NoDup_cons.
Robbert Krebbers's avatar
Robbert Krebbers committed
676
    setoid_rewrite elem_of_cons. setoid_rewrite elem_of_app. naive_solver.
Robbert Krebbers's avatar
Robbert Krebbers committed
677
Qed.
678
Global Instance NoDup_proper: Proper ((≡ₚ) ==> iff) (@NoDup A).
679 680 681 682 683 684 685
Proof.
  induction 1 as [|x l k Hlk IH | |].
  * by rewrite !NoDup_nil.
  * by rewrite !NoDup_cons, IH, Hlk.
  * rewrite !NoDup_cons, !elem_of_cons. intuition.
  * intuition.
Qed.
686 687
Lemma NoDup_lookup l i j x :
  NoDup l → l !! i = Some x → l !! j = Some x → i = j.
688 689 690 691 692 693
Proof.
  intros Hl. revert i j. induction Hl as [|x' l Hx Hl IH].
  { intros; simplify_equality. }
  intros [|i] [|j] ??; simplify_equality'; eauto with f_equal;
    exfalso; eauto using elem_of_list_lookup_2.
Qed.
694 695
Lemma NoDup_alt l :
  NoDup l ↔ ∀ i j x, l !! i = Some x → l !! j = Some x → i = j.
696
Proof.
697 698 699 700
  split; eauto using NoDup_lookup.
  induction l as [|x l IH]; intros Hl; constructor.
  * rewrite elem_of_list_lookup. intros [i ?].
    by feed pose proof (Hl (S i) 0 x); auto.
701
  * apply IH. intros i j x' ??. by apply (inj S), (Hl (S i) (S j) x').
702
Qed.
Robbert Krebbers's avatar
Robbert Krebbers committed
703

704 705 706 707 708 709
Section no_dup_dec.
  Context `{!∀ x y, Decision (x = y)}.
  Global Instance NoDup_dec: ∀ l, Decision (NoDup l) :=
    fix NoDup_dec l :=
    match l return Decision (NoDup l) with
    | [] => left NoDup_nil_2
710
    | x :: l =>
711 712 713 714 715 716 717 718
      match decide_rel (∈) x l with
      | left Hin => right (λ H, NoDup_cons_11 _ _ H Hin)
      | right Hin =>
        match NoDup_dec l with
        | left H => left (NoDup_cons_2 _ _ Hin H)
        | right H => right (H ∘ NoDup_cons_12 _ _)
        end
      end
719
    end.
720
  Lemma elem_of_remove_dups l x : x ∈ remove_dups l ↔ x ∈ l.
721 722 723 724
  Proof.
    split; induction l; simpl; repeat case_decide;
      rewrite ?elem_of_cons; intuition (simplify_equality; auto).
  Qed.
725
  Lemma NoDup_remove_dups l : NoDup (remove_dups l).
726 727 728 729
  Proof.
    induction l; simpl; repeat case_decide; try constructor; auto.
    by rewrite elem_of_remove_dups.
  Qed.
730
End no_dup_dec.
731

732 733 734 735 736 737 738 739 740 741 742 743 744 745 746 747 748 749 750 751 752 753 754 755 756 757 758 759 760 761 762 763 764 765 766 767 768 769 770 771 772 773 774 775 776 777 778 779 780 781 782 783 784 785 786 787 788 789 790 791 792 793 794
(** ** Set operations on lists *)
Section list_set.
  Context {dec : ∀ x y, Decision (x = y)}.
  Lemma elem_of_list_difference l k x : x ∈ list_difference l k ↔ x ∈ l ∧ x ∉ k.
  Proof.
    split; induction l; simpl; try case_decide;
      rewrite ?elem_of_nil, ?elem_of_cons; intuition congruence.
  Qed.
  Lemma NoDup_list_difference l k : NoDup l → NoDup (list_difference l k).
  Proof.
    induction 1; simpl; try case_decide.
    * constructor.
    * done.
    * constructor. rewrite elem_of_list_difference; intuition. done.
  Qed.
  Lemma elem_of_list_union l k x : x ∈ list_union l k ↔ x ∈ l ∨ x ∈ k.
  Proof.
    unfold list_union. rewrite elem_of_app, elem_of_list_difference.
    intuition. case (decide (x ∈ k)); intuition.
  Qed.
  Lemma NoDup_list_union l k : NoDup l → NoDup k → NoDup (list_union l k).
  Proof.
    intros. apply NoDup_app. repeat split.
    * by apply NoDup_list_difference.
    * intro. rewrite elem_of_list_difference. intuition.
    * done.
  Qed.
  Lemma elem_of_list_intersection l k x :
    x ∈ list_intersection l k ↔ x ∈ l ∧ x ∈ k.
  Proof.
    split; induction l; simpl; repeat case_decide;
      rewrite ?elem_of_nil, ?elem_of_cons; intuition congruence.
  Qed.
  Lemma NoDup_list_intersection l k : NoDup l → NoDup (list_intersection l k).
  Proof.
    induction 1; simpl; try case_decide.
    * constructor.
    * constructor. rewrite elem_of_list_intersection; intuition. done.
    * done.
  Qed.
  Lemma elem_of_list_intersection_with f l k x :
    x ∈ list_intersection_with f l k ↔ ∃ x1 x2,
      x1 ∈ l ∧ x2 ∈ k ∧ f x1 x2 = Some x.
  Proof.
    split.
    * induction l as [|x1 l IH]; simpl; [by rewrite elem_of_nil|].
      intros Hx. setoid_rewrite elem_of_cons.
      cut ((∃ x2, x2 ∈ k ∧ f x1 x2 = Some x)
        ∨ x ∈ list_intersection_with f l k); [naive_solver|].
      clear IH. revert Hx. generalize (list_intersection_with f l k).
      induction k; simpl; [by auto|].
      case_match; setoid_rewrite elem_of_cons; naive_solver.
    * intros (x1&x2&Hx1&Hx2&Hx). induction Hx1 as [x1|x1 ? l ? IH]; simpl.
      + generalize (list_intersection_with f l k).
        induction Hx2; simpl; [by rewrite Hx; left |].
        case_match; simpl; try setoid_rewrite elem_of_cons; auto.
      + generalize (IH Hx). clear Hx IH Hx2.
        generalize (list_intersection_with f l k).
        induction k; simpl; intros; [done|].
        case_match; simpl; rewrite ?elem_of_cons; auto.
  Qed.
End list_set.

795
(** ** Properties of the [filter] function *)
796 797 798 799 800 801 802
Section filter.
  Context (P : A → Prop) `{∀ x, Decision (P x)}.
  Lemma elem_of_list_filter l x : x ∈ filter P l ↔ P x ∧ x ∈ l.
  Proof.
    unfold filter. induction l; simpl; repeat case_decide;
       rewrite ?elem_of_nil, ?elem_of_cons; naive_solver.
  Qed.
803
  Lemma NoDup_filter l : NoDup l → NoDup (filter P l).
804 805 806 807 808
  Proof.
    unfold filter. induction 1; simpl; repeat case_decide;
      rewrite ?NoDup_nil, ?NoDup_cons, ?elem_of_list_filter; tauto.
  Qed.
End filter.
Robbert Krebbers's avatar
Robbert Krebbers committed
809

810 811 812
(** ** Properties of the [find] function *)
Section find.
  Context (P : A → Prop) `{∀ x, Decision (P x)}.
813 814
  Lemma list_find_Some l i x :
    list_find P l = Some (i,x) → l !! i = Some x ∧ P x.
815
  Proof.
816 817 818
    revert i; induction l; intros [] ?;
      repeat (match goal with x : prod _ _ |- _ => destruct x end
              || simplify_option_equality); eauto.
819
  Qed.
820
  Lemma list_find_elem_of l x : x ∈ l → P x → is_Some (list_find P l).
821
  Proof.
822
    induction 1 as [|x y l ? IH]; intros; simplify_option_equality; eauto.
823
    by destruct IH as [[i x'] ->]; [|exists (S i, x')].
824 825 826
  Qed.
End find.

827
(** ** Properties of the [reverse] function *)
828 829
Lemma reverse_nil : reverse [] = @nil A.
Proof. done. Qed.
830
Lemma reverse_singleton x : reverse [x] = [x].
831
Proof. done. Qed.
832
Lemma reverse_cons l x : reverse (x :: l) = reverse l ++ [x].
833
Proof. unfold reverse. by rewrite <-!rev_alt. Qed.
834
Lemma reverse_snoc l x : reverse (l ++ [x]) = x :: reverse l.
835
Proof. unfold reverse. by rewrite <-!rev_alt, rev_unit. Qed.
836
Lemma reverse_app l1 l2 : reverse (l1 ++ l2) = reverse l2 ++ reverse l1.
837
Proof. unfold reverse. rewrite <-!rev_alt. apply rev_app_distr. Qed.
838
Lemma reverse_length l : length (reverse l) = length l.
839
Proof. unfold reverse. rewrite <-!rev_alt. apply rev_length. Qed.
840
Lemma reverse_involutive l : reverse (reverse l) = l.
841
Proof. unfold reverse. rewrite <-!rev_alt. apply rev_involutive. Qed.
842 843 844 845 846 847 848 849 850 851
Lemma elem_of_reverse_2 x l : x ∈ l → x ∈ reverse l.
Proof.
  induction 1; rewrite reverse_cons, elem_of_app,
    ?elem_of_list_singleton; intuition.
Qed.
Lemma elem_of_reverse x l : x ∈ reverse l ↔ x ∈ l.
Proof.
  split; auto using elem_of_reverse_2.
  intros. rewrite <-(reverse_involutive l). by apply elem_of_reverse_2.
Qed.
852
Global Instance: Inj (=) (=) (@reverse A).
853 854 855 856
Proof.
  intros l1 l2 Hl.
  by rewrite <-(reverse_involutive l1), <-(reverse_involutive l2), Hl.
Qed.
857 858 859 860 861 862 863 864
Lemma sum_list_with_app (f : A → nat) l k :
  sum_list_with f (l ++ k) = sum_list_with f l + sum_list_with f k.
Proof. induction l; simpl; lia. Qed.
Lemma sum_list_with_reverse (f : A → nat) l :
  sum_list_with f (reverse l) = sum_list_with f l.
Proof.
  induction l; simpl; rewrite ?reverse_cons, ?sum_list_with_app; simpl; lia.
Qed.
865

866 867 868
(** ** Properties of the [last] function *)
Lemma last_snoc x l : last (l ++ [x]) = Some x.
Proof. induction l as [|? []]; simpl; auto. Qed.
869 870 871 872
Lemma last_reverse l : last (reverse l) = head l.
Proof. by destruct l as [|x l]; rewrite ?reverse_cons, ?last_snoc. Qed.
Lemma head_reverse l : head (reverse l) = last l.
Proof. by rewrite <-last_reverse, reverse_involutive. Qed.
873

874 875 876 877 878 879 880
(** ** Properties of the [take] function *)
Definition take_drop i l : take i l ++ drop i l = l := firstn_skipn i l.
Lemma take_drop_middle l i x :
  l !! i = Some x → take i l ++ x :: drop (S i) l = l.
Proof.
  revert i x. induction l; intros [|?] ??; simplify_equality'; f_equal; auto.
Qed.
881
Lemma take_nil n : take n (@nil A) = [].
Robbert Krebbers's avatar
Robbert Krebbers committed
882
Proof. by destruct n. Qed.
883
Lemma take_app l k : take (length l) (l ++ k) = l.
884
Proof. induction l; f_equal'; auto. Qed.
885
Lemma take_app_alt l k n : n = length l → take n (l ++ k) = l.
886 887
Proof. intros ->. by apply take_app. Qed.
Lemma take_app3_alt l1 l2 l3 n : n = length l1 → take n ((l1 ++ l2) ++ l3) = l1.
888
Proof. intros ->. by rewrite <-(assoc_L (++)), take_app. Qed.
889
Lemma take_app_le l k n : n ≤ length l → take n (l ++ k) = take n l.
890
Proof. revert n. induction l; intros [|?] ?; f_equal'; auto with lia. Qed.
891 892 893
Lemma take_plus_app l k n m :
  length l = n → take (n + m) (l ++ k) = l ++ take m k.
Proof. intros <-. induction l; f_equal'; auto. Qed.
894 895
Lemma take_app_ge l k n :
  length l ≤ n → take n (l ++ k) = l ++ take (n - length l) k.
896
Proof. revert n. induction l; intros [|?] ?; f_equal'; auto with lia. Qed.
897
Lemma take_ge l n : length l ≤ n → take n l = l.
898
Proof. revert n. induction l; intros [|?] ?; f_equal'; auto with lia. Qed.
899
Lemma take_take l n m : take n (take m l) = take (min n m) l.
900
Proof. revert n m. induction l; intros [|?] [|?]; f_equal'; auto. Qed.
901
Lemma take_idemp l n : take n (take n l) = take n l.
Robbert Krebbers's avatar
Robbert Krebbers committed
902
Proof. by rewrite take_take, Min.min_idempotent. Qed.
903
Lemma take_length l n : length (take n l) = min n (length l).
904
Proof. revert n. induction l; intros [|?]; f_equal'; done. Qed.
905
Lemma take_length_le l n : n ≤ length l → length (take n l) = n.
Robbert Krebbers's avatar
Robbert Krebbers committed
906
Proof. rewrite take_length. apply Min.min_l. Qed.
907 908
Lemma take_length_ge l n : length l ≤ n → length (take n l) = length l.
Proof. rewrite take_length. apply Min.min_r. Qed.
909
Lemma take_drop_commute l n m : take n (drop m l) = drop m (take (m + n) l).
Robbert Krebbers's avatar
Robbert Krebbers committed
910
Proof.
911
  revert n m. induction l; intros [|?][|?]; simpl; auto using take_nil with lia.
Robbert Krebbers's avatar
Robbert Krebbers committed
912
Qed.
913 914
Lemma lookup_take l n i : i < n → take n l !! i = l !! i.
Proof. revert n i. induction l; intros [|n] [|i] ?; simpl; auto with lia. Qed.
915
Lemma lookup_take_ge l n i : n ≤ i → take n l !! i = None.
Robbert Krebbers's avatar
Robbert Krebbers committed
916
Proof. revert n i. induction l; intros [|?] [|?] ?; simpl; auto with lia. Qed.
917
Lemma take_alter f l n i : n ≤ i → take n (alter f i l) = take n l.
Robbert Krebbers's avatar
Robbert Krebbers committed
918 919 920 921 922
Proof.
  intros. apply list_eq. intros j. destruct (le_lt_dec n j).
  * by rewrite !lookup_take_ge.
  * by rewrite !lookup_take, !list_lookup_alter_ne by lia.
Qed.
923
Lemma take_insert l n i x : n ≤ i → take n (<[i:=x]>l) = take n l.
924 925 926 927 928
Proof.
  intros. apply list_eq. intros j. destruct (le_lt_dec n j).
  * by rewrite !lookup_take_ge.
  * by rewrite !lookup_take, !list_lookup_insert_ne by lia.
Qed.
Robbert Krebbers's avatar
Robbert Krebbers committed
929

930
(** ** Properties of the [drop] function *)
931 932
Lemma drop_0 l : drop 0 l = l.
Proof. done. Qed.
933
Lemma drop_nil n : drop n (@nil A) = [].
Robbert Krebbers's avatar
Robbert Krebbers committed
934
Proof. by destruct n. Qed.
935
Lemma drop_length l n : length (drop n l) = length l - n.
936
Proof. revert n. by induction l; intros [|i]; f_equal'. Qed.
937 938
Lemma drop_ge l n : length l ≤ n → drop n l = [].
Proof. revert n. induction l; intros [|??]; simpl in *; auto with lia. Qed.
939
Lemma drop_all l : drop (length l) l = [].
940
Proof. by apply drop_ge. Qed.
941 942
Lemma drop_drop l n1 n2 : drop n1 (drop n2 l) = drop (n2 + n1) l.
Proof. revert n2. induction l; intros [|?]; simpl; rewrite ?drop_nil; auto. Qed.
943 944 945 946 947 948 949
Lemma drop_app_le l k n :
  n ≤ length l → drop n (l ++ k) = drop n l ++ k.
Proof. revert n. induction l; intros [|?]; simpl; auto with lia. Qed.
Lemma drop_app l k : drop (length l) (l ++ k) = k.
Proof. by rewrite drop_app_le, drop_all. Qed.
Lemma drop_app_alt l k n : n = length l → drop n (l ++ k) = k.
Proof. intros ->. by apply drop_app. Qed.
950 951
Lemma drop_app3_alt l1 l2 l3 n :
  n = length l1 → drop n ((l1 ++ l2) ++ l3) = l2 ++ l3.
952
Proof. intros ->. by rewrite <-(assoc_L (++)), drop_app. Qed.
953 954 955 956 957 958
Lemma drop_app_ge l k n :
  length l ≤ n → drop n (l ++ k) = drop (n - length l) k.
Proof.
  intros. rewrite <-(Nat.sub_add (length l) n) at 1 by done.
  by rewrite Nat.add_comm, <-drop_drop, drop_app.
Qed.
959 960 961
Lemma drop_plus_app l k n m :
  length l = n → drop (n + m) (l ++ k) = drop m k.
Proof. intros <-. by rewrite <-drop_drop, drop_app. Qed.
962
Lemma lookup_drop l n i : drop n l !! i = l !! (n + i).
Robbert Krebbers's avatar
Robbert Krebbers committed
963
Proof. revert n i. induction l; intros [|i] ?; simpl; auto. Qed.
964
Lemma drop_alter f l n i : i < n → drop n (alter f i l) = drop n l.
Robbert Krebbers's avatar
Robbert Krebbers committed
965 966 967 968
Proof.
  intros. apply list_eq. intros j.
  by rewrite !lookup_drop, !list_lookup_alter_ne by lia.
Qed.
969
Lemma drop_insert l n i x : i < n → drop n (<[i:=x]>l) = drop n l.
970 971 972 973
Proof.
  intros. apply list_eq. intros j.
  by rewrite !lookup_drop, !list_lookup_insert_ne by lia.
Qed.
974
Lemma delete_take_drop l i : delete i l = take i l ++ drop (S i) l.
975
Proof. revert i. induction l; intros [|?]; f_equal'; auto. Qed.
976 977 978 979 980 981 982
Lemma take_take_drop l n m : take n l ++ take m (drop n l) = take (n + m) l.
Proof. revert n m. induction l; intros [|?] [|?]; f_equal'; auto. Qed.
Lemma drop_take_drop l n m : n ≤ m → drop n (take m l) ++ drop m l = drop n l.
Proof.
  revert n m. induction l; intros [|?] [|?] ?;
    f_equal'; auto using take_drop with lia.
Qed.
983 984

(** ** Properties of the [replicate] function *)
985
Lemma replicate_length n x : length (replicate n x) = n.
986
Proof. induction n; simpl; auto. Qed.
987 988 989 990 991 992 993 994 995
Lemma lookup_replicate n x y i :
  replicate n x !! i = Some y ↔ y = x ∧ i < n.
Proof.
  split.
  * revert i. induction n; intros [|?]; naive_solver auto with lia.
  * intros [-> Hi]. revert i Hi.
    induction n; intros [|?]; naive_solver auto with lia.
Qed.
Lemma lookup_replicate_1 n x y i :
996
  replicate n x !! i = Some y → y = x ∧ i < n.
997 998 999
Proof. by rewrite lookup_replicate. Qed.
Lemma lookup_replicate_2 n x i : i < n → replicate n x !! i = Some x.
Proof. by rewrite lookup_replicate. Qed.
1000 1001 1002
Lemma lookup_replicate_None n x i : n ≤ i ↔ replicate n x !! i = None.
Proof.
  rewrite eq_None_not_Some, Nat.le_ngt. split.
1003 1004
  * intros Hin [x' Hx']; destruct Hin. rewrite lookup_replicate in Hx'; tauto.
  * intros Hx ?. destruct Hx. exists x; auto using lookup_replicate_2.
1005
Qed.
1006 1007
Lemma insert_replicate x n i : <[i:=x]>(replicate n x) = replicate n x.
Proof. revert i. induction n; intros [|?]; f_equal'; auto. Qed.
1008 1009
Lemma elem_of_replicate_inv x n y : x ∈ replicate n y → x = y.
Proof. induction n; simpl; rewrite ?elem_of_nil, ?elem_of_cons; intuition. Qed.
1010
Lemma replicate_S n x : replicate (S n) x = x :: replicate  n x.
1011
Proof. done. Qed.
1012
Lemma replicate_plus n m x :
Robbert Krebbers's avatar
Robbert Krebbers committed
1013
  replicate (n + m) x = replicate n x ++ replicate m x.
1014
Proof. induction n; f_equal'; auto. Qed.
1015
Lemma take_replicate n m x : take n (replicate m x) = replicate (min n m) x.
1016
Proof. revert m. by induction n; intros [|?]; f_equal'. Qed.
1017
Lemma take_replicate_plus n m x : take n (replicate (n + m) x) = replicate n x.
Robbert Krebbers's avatar
Robbert Krebbers committed
1018
Proof. by rewrite take_replicate, min_l by lia. Qed.
1019
Lemma drop_replicate n m x : drop n (replicate m x) = replicate (m - n) x.
1020
Proof. revert m. by induction n; intros [|?]; f_equal'. Qed.
1021
Lemma drop_replicate_plus n m x : drop n (replicate (n + m) x) = replicate m x.
Robbert Krebbers's avatar
Robbert Krebbers committed
1022
Proof. rewrite drop_replicate. f_equal. lia. Qed.